1994
DOI: 10.1159/000227398
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Lung Cancer: Analysis of Factors Influencing the Response to Treatment and Survival

Abstract: The aims of this study were to identify prognostic factors in patients (pts) with small cell lung cancer and to identify dominant prognostic factors independent of disease stage, to define prognostic subsets through recursive partitioning and amalgamation (RPA) and to analyze the clinical characteristics of long-term survivors. The prognostic significance of 27 pre-treatment variables was evaluated in 144 pts seen at a single institution. The current study confirmed the superior outcome for pts with limited di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 28 publications
3
1
0
Order By: Relevance
“…Our report confirmed previous observations that extent of disease and performance status were strong prognostic factors for OS of SCLC patients [1,3,33,38]. Additionally, in agreement with a previous study, elevated CYFRA 21-1 level was associated with a poor outcome in SCLC patients [24].…”
Section: Discussionsupporting
confidence: 93%
“…Our report confirmed previous observations that extent of disease and performance status were strong prognostic factors for OS of SCLC patients [1,3,33,38]. Additionally, in agreement with a previous study, elevated CYFRA 21-1 level was associated with a poor outcome in SCLC patients [24].…”
Section: Discussionsupporting
confidence: 93%
“…The results suggest, firstly, that women tend to do better than men, irrespective of the particular variable under study. This strong positive prognostic association between female sex and survival is supported by the majority of published reports on the impact of sex on a diagnosis of LS-SCLC (11)(12)(13)(14)(15). In our study, we found an overall fivefold absolute difference in survival at five years favouring women over men.…”
Section: Discussionsupporting
confidence: 85%
“…An incidental finding in these studies, revealed on multivariable analysis, was that despite the negative variables, female sex emerged as a strong positive prognostic factor (8)(9)(10). In itself, this fit with a large number of previous reports demonstrating female sex to be a positive factor in SCLC (11)(12)(13)(14)(15), as compared with a smaller number of reports that show sex has no effect on survival (16,17).…”
supporting
confidence: 64%
“…To date, there are a large number of publications suggesting that women diagnosed with NSCLC (10)(11)(12)(13)(14) small-cell lung cancer (15)(16)(17)(18)(19)(20)(21) have a better prognosis than men. With specific reference to brain metastases and NSCLC, there are retrospective studies suggesting that female gender may have a positive impact on outcomes (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%